Epidemiology of Leptospira Transmitted by Rodents in Southeast Asia - Cosson, Jean-François (Public Library of Science, 2014)
BACKGROUND: Leptospirosis is the most common bacterial zoonoses and has been identified as an important emerging global public health problem in Southeast Asia. Rodents are important reservoirs for human leptospirosis, but epidemiological data is lacking. METHODOLOGY/PRINCIPAL FINDINGS: We sampled rodents living in different habitats from seven localities distributed across Southeast Asia (Thailand, Lao PDR and Cambodia), between 2009 to 2010. Human isolates were also obtained from localities close to where rodents were sampled. The prevalence of Leptospira infection was assessed by real-time PCR using DNA extracted from rodent kidneys, targeting the lipL32 gene. Sequencing rrs and secY genes, and Multi Locus Variable-number Tandem Repeat (VNTR) analyses were performed on DNA extracted from rat kidneys for Leptospira isolates molecular typing. Four species were detected in rodents, L. borgpetersenii (56% of positive samples), L. interrogans (36%), L. kirschneri (3%) and L. weilli (2%), which were identical to human isolates. Mean prevalence in rodents was approximately 7%, and largely varied across localities and habitats, but not between rodent species. The two most abundant Leptospira species displayed different habitat requirements: L. interrogans was linked to humid habitats (rice fields and forests) while L. borgpetersenii was abundant in both humid and dry habitats (non-floodable lands). CONCLUSION/SIGNIFICANCE: L. interrogans and L. borgpetersenii species are widely distributed amongst rodent populations, and strain typing confirmed rodents as reservoirs for human leptospirosis. Differences in habitat requirements for L. interrogans and L. borgpetersenii supported differential transmission modes. In Southeast Asia, human infection risk is not only restricted to activities taking place in wetlands and rice fields as is commonly accepted, but should also include tasks such as forestry work, as well as the hunting and preparation of rodents for consumption, which deserve more attention in future epidemiological studies.